Spatial analysis for prioritizing areas for urban renewal projects in the city of Cali in Colombia - Álvarez, Randy Perea; Gonçalves, Luciana Márcia (National Journal of City Management, 2023)
Most traditional downtown areas in large Latin American cities are undergoing processes of physical deterioration and population decline; thus, alternative urban planning solutions are required to address these issues, including urban renewal as a means to enhance, valorize, improve, and integrate consolidated areas of the city through a change in patterns, with a view to promoting mixed-use development and prevent urban sprawl. This paper proposes a spatial analysis methodology for prioritizing areas for urban renewal projects (AEPRU) in the downtown area of Cali, Colombia, using indicators supported by current urban regulations and fieldwork in the selected study area. The results are reported through tables and thematic cartography produced with Geographic Information Systems (GIS) tools.